"Role of peroxisomes in human lipid metabolism and its importance for neurological development". (10th January 2017) - Wanders, Ronald J.A.; Poll-The, Bwee Tien
Abstract: Peroxisomes play a crucial role in normal neurological development as exemplified by the devastating neurological consequences of a defect in the biogenesis of peroxisomes as in Zellweger syndrome. The underlying basis for the important role of peroxisomes in neurological development resides in the fact that peroxisomes catalyze a number of physiological functions, notably involving the metabolism of different lipids. Indeed, peroxisomes catalyse the beta-oxidative breakdown of certain fatty acids including: (1.) the very long-chain fatty acids C22:0, C24:0, and C26:0; (2.) pristanic acid and (3.) the bile acid intermediates di- and trihydroxycholestanoic acid which cannot be oxidized in mitochondria. Furthermore, peroxisomes catalyze the synthesis of a particular type of lipids, i.e. ether-linked phospholipids, which are highly abundant in brain, especially in myelin. The current state of knowledge with respect to the metabolic role of peroxisomes will be described in this paper with particular emphasis on the role of peroxisomes in brain.